2018
DOI: 10.1016/j.jmb.2018.10.003
|View full text |Cite
|
Sign up to set email alerts
|

TRIM25 Binds RNA to Modulate Cellular Anti-viral Defense

Abstract: TRIM25 is a multi-domain, RING-type E3 ubiquitin ligase of the tripartite motif family that has important roles in multiple RNA-dependent processes. In particular, TRIM25 functions as an effector of RIG-I and ZAP, which are innate immune sensors that recognize viral RNA and induce ubiquitin-dependent anti-viral response mechanisms. TRIM25 is reported to also bind RNA, but the molecular details of this interaction or its relevance to anti-viral defense have not been elucidated. Here, we characterize the RNA-bin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
95
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(108 citation statements)
references
References 28 publications
6
95
3
Order By: Relevance
“…As reported previously, we found that the affinity of the PRY/SPRY domain for pre-let-7 RNA (5.0±1.2 µM, as measured by ITC, Table 2, Figure 2B) is much weaker than for CC-PRY/SPRY (25,26). The RNA-binding of the PRY/SPRY domain alone is therefore not sufficient to explain the high affinity binding of TRIM25.…”
Section: Two Distinct Sites Of the Trim25 Pry/spry Domain Bind To Sinsupporting
confidence: 58%
“…As reported previously, we found that the affinity of the PRY/SPRY domain for pre-let-7 RNA (5.0±1.2 µM, as measured by ITC, Table 2, Figure 2B) is much weaker than for CC-PRY/SPRY (25,26). The RNA-binding of the PRY/SPRY domain alone is therefore not sufficient to explain the high affinity binding of TRIM25.…”
Section: Two Distinct Sites Of the Trim25 Pry/spry Domain Bind To Sinsupporting
confidence: 58%
“…However, other cellular factors present could modulate ZAP's binding specificity. Several groups have shown that the ZAP cofactor TRIM25 can bind cellular and viral RNA, and it has been reported to regulate ZAP binding to Sindbis virus RNA (29,30,(60)(61)(62)(63)(64)(65). Therefore, TRIM25 or other ZAP cofactors could bind specific motifs in viral RNA to determine the sensitivity of the RNA to ZAP-mediated antiviral activity.…”
Section: Discussionmentioning
confidence: 99%
“…Upon induction, some lncRNAs and miRNAs promote or dampen RLR signalling by regulating the gene expression of RLRs or other key molecules in the RLR pathway. In addition, some lncRNAs were shown to directly bind to the RLR sensor protein (in particular RIG-I), or its activator TRIM25, which itself has RNA-binding capacity 101,147,148 (fiG. 4).…”
Section: Regulation By Non-coding Rnas Cellular Non-codingmentioning
confidence: 99%
“…Although RIG-I is well known to be a bona fide RNA sensor, its activator, TRIM25, has recently been shown to also have RNA-binding capacity 101,147,148 . Biochemical and functional studies showed that the ability of TRIM25 to bind RNA is important for its E3 ligase activity and, thus, its positive effect on RIG-I antiviral signalling 148…”
Section: Regulation By Non-coding Rnas Cellular Non-codingmentioning
confidence: 99%